Risk regulation, trade and international law: debating the precautionary principle in and around the WTO - Christiane Gerstetter; Matthias Leonhard Maier (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2005)
The precautionary principle is one of the most contested principles in international law. In the context of trade regulation in particular, it has been a source of concern to those who fear that it might help to justify existing non-tariff barriers to trade or create addi-tional ones. Proponents of the principle, in turn, argue that it is needed to fend off un-warranted health and environmental risks in situations where scientific uncertainty pre-vails, even if this works against the liberalisation of trade. In these contests the question of where and when the precautionary principle should be applied is inextricably linked to the question of what it means in the first place. Starting from the observation that consensus on a precise definition is missing both in legal-political practice and in aca-demic scholarship, the present paper is concerned precisely with those practical inter-pretative contests which result from the principle's ambiguity. We focus on attempts to agree legally binding definitions in the context of international trade regulation. The core of the paper is an empirical analysis of debates on several specific aspects of the precautionary principle, which were at issue during the past decade in four different international institutions: the WTO dispute settlement, some of the WTO's political committees, the Codex Alimentarius Commission (in particular its Committee on Gen-eral Principles), and the conference of states which negotiated the Cartagena Protocol on Biosafety. Differences and similarities among these institutions are then analysed in a comparative perspective, taking up various contested issues one by one. From our findings we derive a set of hypotheses regarding the conditions under which, and the legal or political pathways on which, the precautionary principle (and perhaps other abstract normative ideas of a similar type as well) can make a difference to the out-comes of international decision-making.
Keywords: 330; Vorsorgeprinzip; Normung; WTO-Regeln; Welt